Assessment of Selected Matrix Metalloproteinases (MMPs) and Correlation with Cytokines in Psoriatic Patients. (30th June 2021) - Michalak-Stoma, Anna; Bartosińska, Joanna; Raczkiewicz, Dorota; Kowal, Małgorzata; Krasowska, Dorota; Chodorowska, Grażyna
Abstract : Metalloproteinases (MMPs) and cytokines have a great impact on the pathogenesis of psoriasis. Cytokines, as key mediators of inflammation and autoimmune processes, play a crucial role in the regulation of MMP expression in different cell types. Parallel, MMPs have an influence on cytokine production. This interaction was not well recognized in psoriatic patients. Our study is aimed at assessing the selected serum MMP levels and their correlations with cytokine levels in the serum of psoriatic patients. We observed a significantly elevated level of pro-MMP-1 and MMP-9 in psoriatic patients' serum in comparison to the control group. We did not observe any statistically significant differences of MMP-3 and pro-MMP-10 between the psoriatic patients and the control group. We did not observe any statistically significant differences in all the studied MMP levels between the patients with and without psoriatic arthritis (PsA). MMP-3 level correlated positively with proinflammatory cytokines, i.e., IL-12p/70, IL-17A, and TNF- α as well as MMP-3 and pro MMP-1 correlated positively with IL-4 in the psoriatic patients. In the control group, a positive correlation between pro-MMP-1 and TNF- α was found. These results confirm MMPs and Th1 and Th17 cytokine interaction in the inflammatory regulation in psoriasis.